Wireless multimedia network technologies - Ganesh, Rajamani; Pahlavan, Kaveh, 1951-; Zvonar, Zoran (Kluwer international series in engineering and computer science, 2002)
Wireless Multimedia Network Technologies addresses emerging concepts for developing third generation wireless systems, and covers both theoretically and technologically feasible improvements. Internationally recognized specialists have contributed originals chapters on several core wireless technologies including intelligent and flexible radio access, wireless mobile, ATM networks, channel modeling and internet services, cluster mobile switching centers, and service control quality. Wireless Multimedia Network Technologies is essential reading for professionals, engineers and scientists working in these areas.